Pengaruh Konsolidasi Lahan Perkotaan Terhadap Harga Tanah di Ringintelu, Kelurahan Kalipancur - Kota Semarang - Mulyanti, Wuri (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
Changes in Semarang city is marked by the process of urbanism as an increased need caused widespread land settlements, economic facilities, trade and services as well as network infrastructure. This causes physical changes in the environment and the seizure of the land so that the price of land had become unmanageable. One of the government's efforts to unravel this problem is the structuring of the environment through urban land consolidation program. The program is expected to increase the price of the land, so it will not show the existence of idle land /